Isolation and Characterization of the Outer Membrane of Borrelia hermsii - Shang, Ellen S. (American Society for Microbiology, 1998)
The outer membrane of Borrelia hermsii has been shown by freeze-fracture analysis to contain a low density of membrane-spanning outer membrane proteins which have not yet been isolated or identified. In this study, we report the purification of outer membrane vesicles (OMV) from B. hermsii HS-1 and the subsequent identification of their constituent outer membrane proteins. The B. hermsii outer membranes were released by vigorous vortexing of whole organisms in low-pH, hypotonic citrate buffer and isolated by isopycnic sucrose gradient centrifugation. The isolated OMV exhibited porin activities ranging from 0.2 to 7.2 nS, consistent with their outer membrane origin. Purified OMV were shown to be relatively free of inner membrane contamination by the absence of measurable β-NADH oxidase activity and the absence of protoplasmic cylinder-associated proteins observed by Coomassie blue staining. Approximately 60 protein spots (some of which are putative isoelectric isomers) with 25 distinct molecular weights were identified as constituents of the OMV enrichment. The majority of these proteins were also shown to be antigenic with sera from B. hermsii-infected mice. Seven of these antigenic proteins were labeled with [(3)H]palmitate, including the surface-exposed glycerophosphodiester phosphodiesterase, the variable major proteins 7 and 33, and proteins of 15, 17, 38, 42, and 67 kDa, indicating that they are lipoprotein constituents of the outer membrane. In addition, immunoblot analysis of the OMV probed with antiserum to the Borrelia garinii surface-exposed p66/Oms66 porin protein demonstrated the presence of a p66 (Oms66) outer membrane homolog. Treatment of intact B. hermsii with proteinase K resulted in the partial proteolysis of the Oms66/p66 homolog, indicating that it is surface exposed. This identification and characterization of the OMV proteins should aid in further studies of pathogenesis and immunity of tick-borne relapsing fever.